Modular PV System for Applications in Prosumer Installations with Uncontrolled, Unbalanced and Non-Linear Loads - Paweł Kelm; Rozmysław Mieński; Irena Wasiak (Energies, 2024)
This article proposes a modular system for prosumer installations composed of photovoltaic (PV) panels and energy storage (ES) integrated with the low voltage (LV) network through a common 4-wire AC/DC inverter. The novel idea is a control strategy for the inverter in which additional functionalities are incorporated. Apart from transmitting an active power generated by the PV source, the same inverter is used to manage energy generated by the PV and to compensate for the current unbalance, harmonics (including subharmonics and interharmonics) and reactive power of the prosumer loads. As a result of the algorithm operation, the currents flowing to the prosumer installation are sinusoidal, symmetrical and purely active, which results in voltage balancing and improving voltage waveforms at the point of common coupling (PCC). In this way, with the widespread use of this solution among prosumers, the impact of the prosumer installation on the distribution network is minimized, and power quality (PQ) disturbances such as unacceptable voltage rises, voltage unbalance and harmonics are avoided. The presented approach may be a solution to the problems network operators face nowadays due to the uncontrolled connection of PV sources. The proposed modular system is also beneficial for the prosumer as the instances of unacceptable overvoltage and, consequently, shutdowns of prosumer installations are reduced. The features of the proposed method are shown in relation to other means applied for PQ improvement in the networks with distributed generation. A principle of the control and the involving algorithm for the inverter is presented. The efficiency of the control strategy was tested in a simulation developed in the PSCAD/EMTDC program. The results of simulations are presented, and the proposed solution is concluded.